A administração espanhola no Espírito Santo durante a monarquia dual (1580-1640) - Fernandes, Anna Karoline da Silva (2017)
This is an initial survey on the exercise of positions and ways of enriching the elites of Espírito Santo captaincy. The temporal cutting corresponds to the first decades of the seventeenth century, when the main historical document analyzed was inserted: a letter from King Felipe II to the captain mor of the captaincy of Espírito Santo, on August 13, 1617, ordering an inquiry at the Customs, and the order of 29 witnesses summoned to testify. Our analysis will seek to identify the group of wealthiest individuals in the captaincy, the social origin of the individuals that composed this elite and the economic activities they practiced. In addition, we will study the taxation in the Philippine period, focusing on the activities of the Customs of Espírito Santo captaincy, the institution responsible for tax collection, control of merchandise traffic and inspection of Crown revenues, but also illegal activities, especially those involved with customs activities.